Hubungan Saiz Kumpulan, Jalinan Kumpulan Kerja dan Komitmen Kumpulan Kerja: Satu Kajian Kes di RISDA - Nur Qurratul' Aini, Ismail (2011)
The objective of this study is to identify the relationship between the size of the working group, leader-member exchange quality, team-member exchange quality that impact on the work group affective commitment. A total of 215 staff (n = 215) in RISDA was taken as the sample. Data were analyzed using multiple regression to examine the relationship between variables, namely, leader-member exchange quality, team-member exchange quality and affective commitment. The Pearson correlation analysis was used to test the workgroup size, team-member exchange quality and leader-member exchange quality. Pearson correlation analysis revealed a negative relationship between workgroup size and leader-member exchange quality and team-member exchange quality. This means that the larger of workgroup size, leader-member exchange and team-member exchange quality is decreasing. The results of multiple regression analysis showed a significant positive correlation between leader-member exchange and team-member exchange quality of the affective commitment of the workgroup. Based on these findings, several suggestions were put forward as a business and approach to enhance and sustain commitment in workgroups and networking among member groups and their leaders are directly able to improve organizational performance.